Optimalisasi Daya Saing melalui Inovasi Sistem Pencatatan Keuangan dan Branding Digital pada Pelaku UMKM “Mamidah’s Homemade” di Kelurahan Mekar Sari Balikpapan - Dewi Sartika; Rahmatia Rahmatia; Nurul Aisyah Samila; Siti Masitah; Tiara Maharani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
The field practice program, also known as Innovation Development, is a community service activity conducted by students of STIE Madani Balikpapan aimed at assisting Micro, Small, and Medium Enterprises (MSMEs) in improving their business performance and sustainability in the city of Balikpapan. In this program, Group 6 focuses on the MSME “Mamidah’s Homemade,” located in RT 34, Mekar Sari Subdistrict, Central Balikpapan District, which operates in the home-based food production sector. This activity is designed to provide practical assistance and applied knowledge to address several existing business challenges faced by the MSME. The main objectives of this Innovation Development activity are: (1) to assist in creating a systematic, structured, and consistent financial recording system as a basis for operational planning, evaluation, and decision-making; (2) to support the development of a comprehensive and well-organized business portfolio to strengthen business identity and credibility; and (3) to help business owners enhance their digital branding capabilities through the effective use of online platforms and social media to expand market reach and competitiveness.